Soviet prison camp speech : a survivor's glossary . supplemented by terms from the works of A. I. Solzenicyn - compiled by Meyer Galler and Harlan E. Marquess. (The University of Wisconsin Press, 1972)
Includes bibliography, p. 51-56.